Carotid artery stenting in acute stroke. - Papanagiotou, P; Roth, C; Walter, S; Behnke, S; Grunwald, I; Viera, J; Politi, M; Körner, H; Kostopoulos, P; Haass, A; Fassbender, K; Reith, W (2011)
OBJECTIVES: The purpose of this study is to demonstrate the technical success of carotid artery stenting in acute extracranial internal carotid artery (ICA) occlusion as well as the benefit in clinical outcome. BACKGROUND: Stroke caused by acute occlusion of the ICA is associated with a significant level of morbidity and mortality. For this type of lesion, treatment with standard intravenous thrombolysis alone leads to a good clinical outcome in only 17% of the cases, with a death rate as high as 55%. Recanalization of the occluded ICA can lead to an improvement in acute symptoms of stroke, prevent possible deterioration, and reduce long-term stroke risk. At present, there is no consensus treatment for patients with acute ischemic stroke presenting with severe clinical symptoms due to atherosclerotic occlusion of the extracranial ICA. METHODS: Carotid artery stenting was performed in 22 patients with acute atherosclerotic extracranial ICA occlusion within 6 h of stroke symptom onset. In 18 patients, there was an additional intracranial occlusion at the level of the terminal segment of the ICA (n = 4) and at the level of the middle cerebral artery (n = 14). Intracranial occlusions were either treated with the Penumbra system or the Solitaire stent-based recanalization system, or a combination of mechanical recanalization and intra-arterial thrombolysis. Recanalization results were assessed by angiography immediately after the procedure. The neurologic status was evaluated before and after the treatment with a follow-up as long as 90 days using the National Institutes of Health Stroke Scale and the modified Rankin Scale. RESULTS: Successful revascularization of extracranial ICA with acute stent implantation was achieved in 21 patients (95%). There was no acute stent thrombosis. After successful recanalization of the origin of the ICA, the intracranial recanalization with Thrombolysis In Myocardial Infarction flow grade 2/3 was achieved in 11 of the 18 patients (61%). The overall recanalization rate (extracranial and intracranial) was 14 of 22 patients (63%). Nine patients (41%) had a modified Rankin Scale score of ≤2 at 90 days. The mortality rate was 13.6% at 90 days. CONCLUSIONS: Carotid artery stenting in acute atherosclerotic extracranial ICA occlusion with severe stroke symptoms is feasible, safe, and useful within the first 6 h after symptom onset.